The Formation of Student Character Through Islamic-Based Environmental Education Activities - Sedya Santosa; Izzatin Kamala; Tsaqifa Taqiyya Ulfah (Postgraduate, University of Mataram, 2023)
Maintaining environmental sustainability is the obligation of every human being. This is stated in the verses of the Koran, so self-awareness is needed to prevent environmental damage. The reality is that not everyone can protect the environment optimally. Therefore, it is necessary to instill good character. It is important to instill character education from an early age, especially in elementary/MI students. MIN 4 Gunungkidul shapes student character through Islamic-based environmental education activities. Given this, this study aims to describe the implementation of Islamic-based environmental education activities to shape the noble character of students in MIN 4 Gunungkidul. The method used in this research is a qualitative method with a field research approach. Data collection techniques are interviews, observation, and documentation. Data analysis is carried out by reducing, collecting, presenting data, and ending with conclusions. The research results show that Islamic-based environmental education at MIN 4 Gunung Kidul has been included in the MIN 4 Gunung Kidul Education unit-level curriculum. Islamic-based environmental education activities that are carried out regularly include familiarizing ablution activities with water-saving management before congregational midday prayers, clean Saturday waste collection activities & class picket healthy Saturday movements, and environmental day commemorations. Through the habit of environmental education activities, it is possible to instill in students an attitude of religious character as well as love and care for the environment.